2007
DOI: 10.1080/10731190701586228
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effects of Decreasing Low-Molecular Weight Hemoglobin Components of Hemoglobin-Based Oxygen Carriers (HBOC) in a Swine Model of Severe Controlled Hemorrhagic Shock

Abstract: Hemoglobin-based oxygen carriers (HBOCs) show potential as safe, efficacious, pre-hospital resuscitation fluids. The major criticism of HBOC-201 is its vasoactive property, attributed partially to low-molecular weight (low-MW) tetrameric/dimeric (TD) hemoglobin (Hb) in HBOC solution. Here we sought to determine whether resuscitation with decreasing concentrations of low-MW Hb component of HBOC affects immune responses in hemorrhagic swine. 28 anesthetized swine underwent a soft muscle crush and controlled hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
“…Ortegon et al observed that HBOC-201 had immune-activating potential, especially enhancement of neutrophilic β 2 integrin (CD11b) expression at high concentration in vitro [13]. However, in vivo in moderate and severe controlled hemorrhagic shock (HS) in swine, with the exception of mildly increased plasma levels of the anti-inflammatory Th-2 cytokine, IL-10, HBOC-201 had minimal effects on innate immune responses [14][15][16]. As well, in trauma patients human polymerized hemoglobin (Polyheme) diminished immune activation in comparison with blood transfusions [17].…”
Section: Introductionmentioning
confidence: 99%